Green Exercise Interventions in Heat-Vulnerable Communities: Evaluating Interactions between Urban Greening, Physical Activity, and Heat-Related Mortality - Setyani Dwi Lestari; Puput Aryanto; Nur Hazwani Dzulkefly (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
Heatwaves are becoming more frequent and severe, posing significant health risks, especially for vulnerable populations in urban areas. In response to this, green-exercise interventions, which combine physical activity with exposure to green spaces, offer a promising strategy for mitigating heat-related health risks. This study evaluates the effectiveness of green-exercise interventions in reducing heat-related mortality risks in heat-vulnerable communities. The research follows a longitudinal design, collecting data on physical activity, vegetation indices (NDVI), and heat-related mortality rates in urban areas prone to heatwaves. The findings reveal that green-exercise interventions resulted in up to an 18% reduction in heat-related mortality risks, demonstrating the significant impact of physical activity in natural environments. Moreover, positive correlations were found between increased green space and reduced health risks during heatwaves, emphasizing the importance of urban greening in mitigating the effects of extreme heat. Participants who engaged in outdoor physical activity in green spaces showed greater resilience to heat stress compared to those who opted for indoor exercises, underscoring the added benefits of natural environments for physical and mental health. However, the effectiveness of these interventions varied depending on environmental and behavioral factors, including the quality of green spaces and individual motivation to engage in outdoor activities. This study highlights the need for further research into the long-term effects of green-exercise interventions and the combined impact of socio-economic and environmental factors on health outcomes. The findings suggest that urban greening and physical activity in green spaces should be integrated into public health strategies, particularly in heat-vulnerable areas.